2017
DOI: 10.11604/pamj.2017.28.67.9934
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ownership, usage and knowledge of Insecticide Treated Nets (ITNs) in Malaria Prevention in the Hohoe Municipality, Ghana

Abstract: IntroductionMalaria remains one of the top five killer diseases in sub-Saharan Africa (SSA) and its burden is skewed towards pregnant women and children under five. Insecticide Treated Bed-Net (ITN) usage is considered one of the most cost-effective, preventive interventions against malaria. This study sought to assess ownership, usage, effectiveness, knowledge, access and availability of ITNs among mothers with children under five in the Hohoe municipality.MethodsIn August 2010 a cross-sectional survey was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
36
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 25 publications
14
36
3
Order By: Relevance
“…In Uganda and Zimbabwe, bed net utilization was signi cantly in uenced by the density of bed nets in the households (14,36). This was also corroborated by the 2007 national malaria indicator survey in Ethiopia (44), 2009 community based Survey in Madagascar (33). However, the proportion of bed nets in Adami Tulu did not in uenced utilization of bed nets by children aged less than 5 years (29) and this difference might be related to difference in the attitude towards the bed net utilization on the prevention of malaria.…”
Section: Discussionmentioning
confidence: 54%
“…In Uganda and Zimbabwe, bed net utilization was signi cantly in uenced by the density of bed nets in the households (14,36). This was also corroborated by the 2007 national malaria indicator survey in Ethiopia (44), 2009 community based Survey in Madagascar (33). However, the proportion of bed nets in Adami Tulu did not in uenced utilization of bed nets by children aged less than 5 years (29) and this difference might be related to difference in the attitude towards the bed net utilization on the prevention of malaria.…”
Section: Discussionmentioning
confidence: 54%
“…Also, more than half (55%) of the respondents in this study reported that they had a family history of hypertension. This is much higher than the 35.7 % reported in a study on the frequency of hypertension and prehypertension among adults in Hohoe, a municipality in the Volta region of Ghana [ 20 ]. A review of population-based studies on hypertension in Ghana indicated that hypertension was positively associated with a positive family history of hypertension [ 21 ].…”
Section: Discussionmentioning
confidence: 63%
“…Despite significant findings on the effectiveness and availability of vector control approaches such as insecticide-treated nets (ITNs), lost-lasting insecticidal nets (LLIN), insecticides, Rapid Diagnostic Test kits, anti-malaria medicines, and removal of standing water sources, these recommendations do not always translate well to local settings and cultures, where social and behavioral aspects of malaria can restrain appropriate health-seeking, prevention, and treatment behaviors. 6,[11][12][13][14][15][16][17][18] For example, educative programs about mosquito nets and increased availability of mosquito nets may be insufficient to increase the use of ITNs and knowledge of malaria prevention. 19 To promote awareness of preventive measures for malaria such as wide-scale use of ITNs and environmental conditions that can serve as breeding grounds for the parasite-carrying mosquito, greater attention should be placed on how information about malaria is relayed.…”
Section: Study Sitementioning
confidence: 99%